Anxiety disorders in women: does gender matter to treatment? - Kinrys,Gustavo (2005)
Women have a substantially higher risk of developing lifetime anxiety disorders compared with men. In addition, research evidence has generally observed an increased symptom severity, chronic course, and functional impairment in women with anxiety disorders in comparison to men. However, the reasons for the increased risk in developing an anxiety disorder in women are still unknown and have yet to be adequately investigated. Evidence from various studies has suggested that genetic factors and female reproductive hormones may play important roles in the expression of these gender differences. The significant differences in onset and course of illness observed in men and women diagnosed with anxiety disorders warrants investigations into the need of differential treatment; however, evidence of gender differences in treatment response to different anxiety disorders are varying and remain largely inconclusive. This article reviews the prevalence, epidemiology, and phenomenology of the major anxiety disorders in women, as well as the implications of such differences for treatment.